The Profiling of Awareness of Access and Use of Finance: A Case Study of SMEs In Karachi - Waheed, Warisha; Siddiqui, Danish Ahmed (Asian Development Policy Review, 2019)
This article focuses on factors that affect access to finance by small-to-medium enterprises (SMEs) in Pakistan and the factors that affect their performance. The study also analysed the association between the characteristics of SME owners, owners’ needs for finance and the difficulties they face in accessing finance from Pakistani banks, and how that difficulty affects their performance. The study also identified the business environments in which SMEs operate in Pakistan. 150 SMEs from Pakistan were selected and questionnaires used to collect data. The study examines how SME owners’ characteristics - education,training, and experience – influence their enterprises’ performance. Firms’ attributes such as business size, business ownership type, and the availability of a business plan were also examined, as well as the difficulties experienced by SMEs in obtaining finance, and the overall demand for finance by Pakistani SMEs. It was found that the primary causes of failure to obtain finance were the absence of insurance, poor budgetary management, unfeasible strategies, deficient data, and high loan fees. The findings also show that interior and exterior influences including the accessibility of capital, consumer loyalty and promotion of the SME were significant factors affecting performance.